Drying of horse chestnut (Aesculus indica) starch: drying kinetics and morphology - Rafiq, Syed Insha; Rafiq, Syed Mansha; Muzaffar, Khalid; Saxena, D C (Journal of Postharvest Technology, 2021)
An investigation was carried out to study the drying kinetics of Horse Chestnut starch dried in hot air oven and the impact of temperature on morphology of starch granules. Starch extracted from Horse Chestnut flour was dried at different temperatures of 30, 40 and 50°C. The experimental drying data obtained was then fitted to six different theoretical and/or empirical drying models. Nonlinear regression analysis was performed to find the best fit model. Among all the models, the Diffusion model was found to best fit the experimental data. The activation energy (Ea) for drying process was 13.66kJmol-1. Morphological analysis of the starch revealed that starch dried at 40°C showed better quality with smooth surface of starch granules and thus may be considered as a limiting temperature for drying of Horse Chestnut starch.